Building an In-vitro Cell Model to Study Cellular Basis of Maturation Timing: A Proof of 3D Cell Culture Methodology in Atlantic Salmon Adipose Tissue - Koskinen, Elisabeth (Helsingin yliopisto)
Three-dimensional (3D) cellular cultures have been shown to represent tissue formations and functions more accurately than two-dimensional (2D) cultures and have been successfully utilized more accurately in model organisms, e.g., to understand cellular modular functions. However, the applications in non-model organisms are limited, and to our knowledge have not been implemented in ectotherms. At an ecological scale, the technique can enhance our understanding by providing insights on cellular and tissue level molecular mechanisms. A potential implementation of this method in Atlantic salmon is to elucidate the molecular function of the vestigial-like 3 (vgll3) gene, which plays a central role in salmonid maturity, potentially by regulating energy allocation via regulating adipogenesis. In this thesis, a proof of principle study was implemented, where the feasibility of obtaining and maintaining a suspension 3D adipose tissue culture in Atlantic salmon (Salmo salar) was assessed. The harvested visceral white adipose tissue from around the intestinal tissue of mature Atlantic salmon (salmon past smolt stage) was first separated into stromal vascular fraction (SVFs) and mature adipose fraction (MAFs). SVFs contain preadipocytes (precursors of adipocyte cells) in addition to a variety of other cell types. MAFs are mature adipocytes. Both MAFs and SVFs were successfully maintained in-vitro for over four weeks. SVFs were then successfully differentiated into mature adipocytes, demonstrating the feasibility of studying adipogenesis in Atlantic salmon. Proof of this methodology and its further implications may help us to understand the cellular functions of vgll3 and may subsequently help to better understand its causal relation to the maturation process in Atlantic salmon.